2022
DOI: 10.1038/s41598-022-14661-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of geranium oil formulations effective for control of phenotypic resistant cattle tick Rhipicephalus annulatus

Abstract: The aim of the present study was to evaluate in vitro and in vivo the acaricidal activity of two forms of geranium (Pelargonium graveolens) (PG). These two forms were the P. graveolens essential oil nanoemulsion (PGN), and the PG in combination with the sesame oil (SO), PGSO). These forms were first evaluated in vitro for their adulticidal, ovicidal, and larvicidal activities against the different stages of acaricide-resistant Rhipicephalus annulatus (Say). Geranium nanoemulsion was prepared and then character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…In the field study, BA combined with deltamethrin reduced R. annulatus tick count by 30.6% as compared with deltamethrin alone (4.7%) after 14 days PT. This finding agreed with previous studies in the same area that confirmed deltamethrin's inadequacy in tick control (Arafa et al, 2021; Ibrahium et al, 2022). Deltamethrin was shown to be insufficient against R. microplus in India, according to Stuti and Chhotey (2011).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the field study, BA combined with deltamethrin reduced R. annulatus tick count by 30.6% as compared with deltamethrin alone (4.7%) after 14 days PT. This finding agreed with previous studies in the same area that confirmed deltamethrin's inadequacy in tick control (Arafa et al, 2021; Ibrahium et al, 2022). Deltamethrin was shown to be insufficient against R. microplus in India, according to Stuti and Chhotey (2011).…”
Section: Discussionsupporting
confidence: 93%
“…In the field study, BA combined with deltamethrin reduced the same area that confirmed deltamethrin's inadequacy in tick control (Arafa et al, 2021;Ibrahium et al, 2022). Deltamethrin was shown to be insufficient against R. microplus in India, according to Stuti andChhotey (2011).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Additionally, an 8:2 binary mixture of sesame oil and clove oil had synergistic effects against adult Callosobruchus maculatus (Soe et al, 2019). In a recent study conducted by Ibrahium et al (2022), sesame oil and geranium oil possess synergistic effect in controlling cattle ticks.…”
Section: Introductionmentioning
confidence: 99%